Will a green color and nature images make consumers pay more for a green product?. Issue 3 (15th February 2021) - Samaraweera, Manoshi; Sims, Jeanetta D.; Homsey, Dini M.
Abstract : Purpose: Would a green color label increase the dollar amount consumers are willing to pay for a green product? Would nature images (such as a leaf or flower) on the label have the same effect? This paper aims to examine the role of these labeling strategies in influencing consumer willing to pay. Design/methodology/approach: Using a 2 × 3 experiment, the authors empirically test the research questions across two studies: in the controlled-lab setting with 160 students (Study 1) and in a field-setting with 268 consumers shopping at a grocery store (Study 2). Findings: Results are consistent across both studies. Surprisingly, participants are willing to pay more for the product when it has a white-toned label rather than a green-toned one. Follow-up path analysis, with Study 2 data, reveals that a white-toned label has both an indirect (through more favorable evaluations of the product's environmental friendliness), as well as a direct impact on willingness to pay. In providing a post hoc explanation, it is argued that a white-toned label better directs attention towards the claim signaling the product's eco-friendliness, while providing a "clean", "high-quality" look. In both studies however, nature images on the label did not have a significant effect. Practical implications: Insights are particularly interesting for practitioners seeking to better label/package green products. Originality/value: This investigation is the first to empirically examine how color and images on the label influence the dollar amount consumers are willing to pay for a green product. Findings reveal that counter to common belief, the heavy use of the color green on eco-friendly product labels might not be appropriate; a predominantly white-toned label works better.